2013
DOI: 10.3109/15376516.2013.843108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creatine supplementation on biomarkers of hepatic and renal function in young trained rats

Abstract: Creatine supplementation has been widely used by athletes and young physical exercise practioneers in order of increasing muscle mass and enhancing athletic performance, but their use/overuse may represent a health risk on hepatic and renal impaired function. In this study, we evaluated the effects of 40 days of oral creatine supplementation on hepatic and renal function biomarkers in a young animal model. Wistar rats (5 weeks old) were divided in five groups (n = 7): control (CONTR), oral creatine supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
5
0
3
Order By: Relevance
“…Souza et al ( 2009 ) found that rodents consuming higher doses of dietary creatine experienced a significant rise in liver enzymes panel, accompanied by structural alterations indicating hepatic damage. These findings were corroborated in another preclinical study where creatine provoked an increase in several hepatic biomarkers (Souza et al, 2013 ). In another study, ethanol intake combined with creatine exacerbated cell degeneration and fat accumulation, hepatic expression of genes related to ethanol metabolism, oxidative stress, and inflammation, and promoted oxidative stress and elevated plasma alanine aminotransferase (Marinello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 64%
“…Souza et al ( 2009 ) found that rodents consuming higher doses of dietary creatine experienced a significant rise in liver enzymes panel, accompanied by structural alterations indicating hepatic damage. These findings were corroborated in another preclinical study where creatine provoked an increase in several hepatic biomarkers (Souza et al, 2013 ). In another study, ethanol intake combined with creatine exacerbated cell degeneration and fat accumulation, hepatic expression of genes related to ethanol metabolism, oxidative stress, and inflammation, and promoted oxidative stress and elevated plasma alanine aminotransferase (Marinello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 64%
“…In our study, a week of CrS significantly increased creatinine and CK plasma levels, and simultaneously reduced globulins and T3 plasma levels, mimicking a condition that characterizes impaired renal function [ 53 ]. Understanding that CrS may contribute to renal dysfunction misdiagnosis because moderate increases of creatinine levels are to be expected [ 54 , 55 ], evidence indicates that creatine supplementation would overload kidney function [ 1 , 56 ]. Although several studies ensure the safety of CrS [ 57 61 ], even in individuals at risk for kidney disease, daily doses of 20 g were associated with the formation of carcinogenic heterocyclic amines and to deleterious molecules such as methylamine and formaldehyde that promote cross-linkage between proteins and DNA damage-induced changes to renal structures [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this was the first study that evaluated morphological aspects, both histopathological and histomorphometric, of pancreatic and renal tissues and the redox state in diabetic rats induced by STZ, supplemented or not with creatine. The literature shows several studies describing the presence of clinical and biochemical parameters [ 23 , 27 , 37 , 38 , 56 , 57 , 58 ]. However, creatine supplementation studies in DM without evaluating morphological parameters and tissue injury are quite recurrent.…”
Section: Discussionmentioning
confidence: 99%